Design and Analysis of 8-bit Array, Carry Save Array, Braun, Wallace Tree and Vedic Multipliers - S. , Nagaraj; B. , Vamsi Krishna; Naresh, Ganekanti; P., K. Anand Prem (International Journal of Psychosocial Rehabilitation, 2020)
Multiplier is the basic building block for several applications, like digital signal processing processors and digital image processing. In this paper, we have designed an 8-bit array, a carry-save array, a Braun, Wallace tree, and a Vedic multiplier. And we have analyzed speed, area, and power. The design was implemented using Verilog HDL coading, simulated, and synthesized using the Xilinx Tool.